2022
DOI: 10.3389/fonc.2022.1029282
|View full text |Cite
|
Sign up to set email alerts
|

Small cell lung cancer transformation and tumor heterogeneity after sequential targeted therapy and immunotherapy in EGFR-mutant non-small cell lung cancer: A case report

Abstract: BackgroundHistological transformation from non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) is one of mechanisms of the acquired resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKI). However, SCLC transformation and tumor heterogeneity have never been reported in sequential targeted therapy and immunotherapy.Case presentationHere, we described a patient with advanced EGFR-mutant NSCLC, who received erlotinib and underwent the resistance with EGFR T790M (–). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…In other studies, Ferrer et al and Wang et al demonstrated that 39 of 48 patients (81 %) and 22 of 25 patients (88 %) were receiving EGFR-TKIs at the time of transformation [ 7 , 10 ], suggesting that some patients with EGFR -mutated NSCLC show SCLC transformation after the cessation of EGFR-TKIs. Therefore, we performed a literature review [ 3 , 9 , [11] , [12] , [13] , [14] , [15] ] and summarized these cases ( Table 1 ). In most of these reports, SCLC transformation was observed within two to seven months of cessation of TKI administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, Ferrer et al and Wang et al demonstrated that 39 of 48 patients (81 %) and 22 of 25 patients (88 %) were receiving EGFR-TKIs at the time of transformation [ 7 , 10 ], suggesting that some patients with EGFR -mutated NSCLC show SCLC transformation after the cessation of EGFR-TKIs. Therefore, we performed a literature review [ 3 , 9 , [11] , [12] , [13] , [14] , [15] ] and summarized these cases ( Table 1 ). In most of these reports, SCLC transformation was observed within two to seven months of cessation of TKI administration.…”
Section: Discussionmentioning
confidence: 99%
“…19 del erlotinib (more than 2 years) NA a 2 van Riel S et al [ 13 ] 42 F NA a erlotinib (10 months) CBDCA + PTX, erlotinib, DTX 2 Zakowski MF et al [ 9 ] 45 F NA a erlotinib (18 months) mitomycin + vinblastine 2 Morinaga R et al [ 12 ] 46 F Ex. 19 del gefitinib (10 months) NA a 5 Yang MH et al [ 15 ] 50 M Ex. 19 del erlotinib (6.5 months) CBDCA + PTX + toripalimab 6.6 Popat S et al [ 11 ] 46 F Ex.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies have shown that small cell transformation is commonly recognized as one of the resistance mechanisms to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in EGFR-mutant NSCLC, which accounts for 3-14% of resistant cases. [9][10][11] In addition, small cell transformation in advanced NSCLC patients treated with EGFR-TKIs is associated with poor survival outcomes. 12 Recently, small cell transformation is extremely rare for advanced NSCLC patients who have failed immunotherapy.…”
Section: Introductionmentioning
confidence: 99%